Electromagnetic wave absorption of coconut fiber-derived porous activated carbon - Yusuf, J.Y. (Sociedad Espanola de Ceramica y Vidrio, 2021)
In this study, porous carbon has been prepared through potassium hydroxide (KOH) activation of coconut fiber (CF) and subsequent carbonization in the presence of an inert gas. The activated carbons (AC) were prepared via carbonization of the precursor at different temperatures. Subsequently, their electromagnetic wave absorption (EMWA) performance was investigated at X-band frequency. The phase crystallinity, porous features, and degree of graphitization of the activated carbons were studied using XRD, nitrogen adsorption/desorption isotherm, and Raman spectroscopy, respectively. Using the BET method, the activated carbon prepared at 750 °C displayed a high specific surface area of 602.9 m2 g-1 and an average pore size of 6 nm, which confirms the extant of mesopores. The EMWA was studied using COMSOL Multiphysics software based on the finite element method. Results show that the activated carbon prepared at 750 °C attained an optimal reflection loss of -45.6 dB at 10.96 GHz with a corresponding effective bandwidth of 3.5 GHz at a thickness of 3.0 mm. In conclusion, this study interestingly shows that porous carbon obtained from coconut fiber has great potential for attenuating electromagnetic waves. © 2021 SECV.